Ferrous Iron-Dependent Volatilization of Mercury by the Plasma Membrane of Thiobacillus ferrooxidans - Iwahori, Kenji (American Society for Microbiology, 2000)
Of 100 strains of iron-oxidizing bacteria isolated, Thiobacillus ferrooxidans SUG 2-2 was the most resistant to mercury toxicity and could grow in an Fe(2+) medium (pH 2.5) supplemented with 6 μM Hg(2+). In contrast, T. ferrooxidans AP19-3, a mercury-sensitive T. ferrooxidans strain, could not grow with 0.7 μM Hg(2+). When incubated for 3 h in a salt solution (pH 2.5) with 0.7 μM Hg(2+), resting cells of resistant and sensitive strains volatilized approximately 20 and 1.7%, respectively, of the total mercury added. The amount of mercury volatilized by resistant cells, but not by sensitive cells, increased to 62% when Fe(2+) was added. The optimum pH and temperature for mercury volatilization activity were 2.3 and 30°C, respectively. Sodium cyanide, sodium molybdate, sodium tungstate, and silver nitrate strongly inhibited the Fe(2+)-dependent mercury volatilization activity of T. ferrooxidans. When incubated in a salt solution (pH 3.8) with 0.7 μM Hg(2+) and 1 mM Fe(2+), plasma membranes prepared from resistant cells volatilized 48% of the total mercury added after 5 days of incubation. However, the membrane did not have mercury reductase activity with NADPH as an electron donor. Fe(2+)-dependent mercury volatilization activity was not observed with plasma membranes pretreated with 2 mM sodium cyanide. Rusticyanin from resistant cells activated iron oxidation activity of the plasma membrane and activated the Fe(2+)-dependent mercury volatilization activity of the plasma membrane.